Attractiveness of light-emitting diodes (LEDs) of different wavelengths to the South American rice water weevil - Eduardo Rodrigues Hickel (Arquivos do Instituto Biológico, 2018)
ABSTRACT: The South American rice water weevil Oryzophagus oryzae (Costa Lima) (Coleoptera: Curculionidae) is a key pest of irrigated rice in Brazil. Light traps could be used as an integrated pest management (IPM) strategy since these weevils have strong phototropism. Thus, the aim of this study was to search the attractiveness of LEDs of different wavelengths to O. oryzae to define the best light-emitting diodes (LED) arrangement to build the lamp of photovoltaic light traps. LEDs of different wavelengths were tested in a dark room with a hexagonal arena with exits to light sources. Groups of 200 insects were released in the center of the arena and captured at the end of exposure time in plastic bags placed in the exits. The LEDs in the short-wave band of the light spectrum (365 and 460 nm) and white LEDs, as well as the light mix of 365 with 460 nm or white LEDs, were attractive to O. oryzae. Beyond the LEDs with ultraviolet (UV) spectrum, the LEDs above 380 nm were the most attractive and, this way, might be used to build LED lamps of photovoltaic light traps.